Clinical Efficacy and Safety of Shashen Maidong Decoction in the Treatment of Pediatric Mycoplasma Pneumonia: A Systematic Review and Meta-Analysis - Wang, Jiawei; Ma, Xiao; Wei, Shizhang; Yang, Tao; Tong, Yuling; Jing, Manyi; Wen, Jianxia; Zhao, Yanling (Frontiers in Pharmacology, 2021)
Objective: This study was intended to provide data to support the effect of Shashen Maidong Decoction in improving mycoplasma pneumonia in pediatric patients through systematic evaluation. Methods: PubMed, the Web of Science, EMbase, CNKI, CQVIP, Wan-Fang, and CBM databases were comprehensively searched from established in June 2021. Randomized controlled trials (RCTs) of TRQI were selected by screening the literature and extracting information. The Cochrane RCT Evaluation Manual was used to evaluate the methodological quality of all included studies, and Meta-analysis was performed using Stata 14.0 and Review Manager 5.4 software. Results: A total of 1127 patients from 12 clinical studies met the inclusion criteria. Meta-analysis results showed that the treatment group of Shashen Maidong Decoction was able to significantly increase the overall efficiency level and significantly reduce the incidence of adverse reactions, time for disappearance of cough, time for relief of cough, time for defervescence, time for disappearance of lung rales, time for chest X-ray resurgence, T lymphocyte subpopulation (CD3+) and tumor necrosis factor-α (TNF-α) and other index levels (P<0.05). Conclusion: Shashen Maidong Decoction has a significant improvement in the levels of relevant indexes in pediatric mycoplasma pneumonia, which provides a basis for the safety and efficacy of pediatric mycoplasma pneumonia. However, due to the small sample size included in the study, the study quality was not high, and more randomized controlled trials of high quality are required for further validation.